SLEEP DISORDERS IN PREGNANT WOMEN (REVIEW OF LITERATURE) (Western European Journal of Medicine and Medical Science, 2024)
This review article is devoted to the study of sleep disorders in pregnant women. Research has shown that 50% to 80% of pregnant women suffer from various sleep disorders, such as insomnia, obstructive sleep apnea syndrome, restless legs syndrome, and night awakenings. These problems are associated with physiological changes, hormonal shifts, weight gain, and emotional factors, including anxiety and stress. This article discusses the main factors affecting the quality of sleep in pregnant women and their impact on the health of the mother and fetus, as well as possible methods of prevention. The purpose of the article is to provide a comprehensive analysis of the causes and consequences of sleep disorders during pregnancy